2021
DOI: 10.1007/s00217-021-03802-1
|View full text |Cite
|
Sign up to set email alerts
|

Selected dried fruits as a source of nutrients

Abstract: Dried fruits are an excellent alternative to unhealthy snacks. Twelve commercially available dried fruits were selected: dates, raisins, prunes, Goji berry, chokeberry, rose hip, sea buckthorn, berberis, physalis, haritaki, noni and juniper. The nutritional value in terms of moisture, ash, protein, fat, carbohydrate, dietary fiber, energy value, mineral composition, antioxidant activity and tannins was compared. It is a novelty in the literature in relation to the particular analytes (e.g., minerals, tannins) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
(35 reference statements)
2
10
0
Order By: Relevance
“…Dietary fiber is an essential aspect of good nutrition. The fiber content measured up to 16% for both B. nummularia and B. atrocarpa , which is in line with previous reports of other berberis fruit [ 27 ]. Researchers suggest consumption of the dried-fruit, which are rich in dietary fiber, is beneficial for weight control and reducing blood glucose [ 28 ] due to increased satiety and intestinal regulation [ 29 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Dietary fiber is an essential aspect of good nutrition. The fiber content measured up to 16% for both B. nummularia and B. atrocarpa , which is in line with previous reports of other berberis fruit [ 27 ]. Researchers suggest consumption of the dried-fruit, which are rich in dietary fiber, is beneficial for weight control and reducing blood glucose [ 28 ] due to increased satiety and intestinal regulation [ 29 ].…”
Section: Resultssupporting
confidence: 91%
“…B. atrocarpa fruit has low levels (10 ± 0.3 mg/100 g) of iron (Fe) and Cu (1 ± 0.0 mg/100 g) content, but not present in B. nummularia . Noticeably, the content of Na in B. nummularia was significantly higher than in B. atrocarpa and other berberis [ 2 , 27 ]. This is related to the growing conditions of this species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the advanced freeze-drying technique contributes to preserving goji berries´ bioactive compounds (phenolic acids, vitamin C, monoterpenes, and carotenoids) and nutrients. This results in high-quality, dried goji snacks which are light, crunchy, with original taste, preserved texture, and a healthy alternative to sweet snacks [ 124 , 127 , 128 ]. In addition, Song et al (2018) reported that the application of advanced freeze-dried with instant controlled pressure drop drying for the dehydration of goji berries resulted in excellent crispness and texture, as well as high contents of total polysaccharides (139.8 g/kg) and carotenoids (2.43 g/kg) in dried products [ 121 ].…”
Section: Processing Of Goji Berriesmentioning
confidence: 99%